Europe and the Eastern other : comparative perspectives on politics, religion and culture before the Enlightenment - Bashir, Hassan, 1971- (Lexington Books, 2013)
Europe and the Eastern Other critically evaluates and supports the argument for adopting an inter-cultural or comparative approach in western political theory. Hassan Bashir examines the encounters between Europeans and their eastern others before the European Enlightenment and illustrates that the West's cultural others have played a foundational role in developing a distinct western cultural self-understanding. This analysis includes records of eyewitness accounts of European visitors in Eastern lands during the medieval and early modern periods, including William of Rubruck's account of the Mongol lands in mid-thirteenth century, observations of the first Jesuit mission in the court of Mughal Indian emperor Akbar the Great, and circumstances in late Ming China as recorded in the journals of Jesuit missionary and scholar Matteo Ricci. This work illustrates the dynamism and complexity involved in an inter-cultural encounter and highlights the fact that cultural self-understanding is often deeply rooted in how we understand our cultural others.